The pathological Trento variant of alpha‐1‐antitrypsin (E75V) shows nonclassical behaviour during polymerization. (8th June 2017) - Miranda, Elena; Ferrarotti, Ilaria; Berardelli, Romina; Laffranchi, Mattia; Cerea, Marta; Gangemi, Fabrizio; Haq, Imran; Ottaviani, Stefania; Lomas, David A.; Irving, James A.; Fra, Annamaria
Abstract : Severe alpha‐1‐antitrypsin deficiency (AATD) is most frequently associated with the alpha‐1‐antitrypsin (AAT) Z variant (E342K). ZZ homozygotes exhibit accumulation of AAT as polymers in the endoplasmic reticulum of hepatocytes. This protein deposition can lead to liver disease, with the resulting low circulating levels of AAT predisposing to early‐onset emphysema due to dysregulation of elastinolytic activity in the lungs. An increasing number of rare AAT alleles have been identified in patients with severe AATD, typically in combination with the Z allele. Here we report a new mutation (E75V) in a patient with severe plasma deficiency, which we designate Trento. In contrast to the Z mutant, Trento AAT was secreted efficiently when expressed in cellular models but showed compromised conformational stability. Polyacrylamide gel electrophoresis (PAGE) and ELISA‐based analyses of the secreted protein revealed the presence of oligomeric species with electrophoretic and immunorecognition profiles different from those of Z and S (E264V) AAT polymers, including reduced recognition by conformational monoclonal antibodies 2C1 and 4B12. This altered recognition was not due to direct effects on the epitope of the 2C1 monoclonal antibody which we localized between helices E and F. Structural analyses indicate the likely basis for polymer formation is the loss of a highly conserved stabilizing interaction between helix C and the posthelix I loop. These results highlight this region as important for maintaining native state stability and, when compromised, results in the formation of pathological polymers that are different from those produced by Z and S AAT. Abstract : A novel mutant of alpha1 antitrypsin (E75V‐AAT) forms polymers different from the common Z AAT variant: polymers of Z AAT accumulate readily within the endoplasmic reticulum (ER) and are poorly secreted, while E75V polymers are shorter, have different structural features and are secreted from cells at almost wild‐type levels.